2020
DOI: 10.1002/dmrr.3284
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions to enhance healing of chronic foot ulcers in diabetes: a systematic review

Abstract: The management of diabetic foot ulcers (DFU) remains a challenge, and there is continuing uncertainty concerning optimal approaches to wound healing. The International Working Group of the Diabetic Foot (IWGDF) working group on wound healing has previously published systematic reviews of the evidence in 2008, 2012 and 2016 to inform protocols for routine care and to highlight areas which should be considered for further study. The working group has now updated this review by considering papers on the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 199 publications
(390 reference statements)
0
68
0
1
Order By: Relevance
“…For each assessable outcome we graded the quality of evidence based on the risk of bias of included studies, effect sizes, presence of inconsistency, and evidence of publication bias (the latter where appropriate). We then rated the quality of evidence as “high,” “moderate,” or “low.” The systematic review supporting this guideline is published separately …”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…For each assessable outcome we graded the quality of evidence based on the risk of bias of included studies, effect sizes, presence of inconsistency, and evidence of publication bias (the latter where appropriate). We then rated the quality of evidence as “high,” “moderate,” or “low.” The systematic review supporting this guideline is published separately …”
Section: Methodsmentioning
confidence: 96%
“…The systematic review supporting this guideline is published separately. 4 Third, we formulated recommendations to address each clinical question. We aimed to be clear, specific, and unambiguous on what we recommend, for which persons, and under what circumstances.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…55 In the recently published systematic review of the effectiveness of interventions to enhance the healing of chronic ulcers of the foot in diabetes, the International Working Group on Diabetic Foot (IWGDF) concluded that apart from sharp debridement, there was inadequate evidence to establish the superiority of one debridement over another. 60 At present, the IWGDF has not recommended the use of ultrasound-based technology for debridement nor in DFU healing given the paucity of evidence around clinical effectiveness. 61 The everyday role of ultrasound debridement technology will, therefore, be in situations where other debridement methods, such as sharp debridement, may cause inordinate pain or in which are resistant to conventional debridement techniques.…”
Section: Position In International Guidelinesmentioning
confidence: 99%
“…First, we do agree that the results of recent hyperbaric oxygen therapy (HBOT) trials are inconsistent and generally fail to provide robust evidence to support the adjunctive use of HBOT for DFUs ( 3 5 ). Much of the failure to provide consistent results is due to study design deficiencies; heterogeneity in study populations, inclusion criteria, and outcome measures (DFU healing vs. amputation); lack of sham controls; and loss of subjects because of adverse events and early terminations ( 6 , 7 ). Furthermore, intention-to-treat (ITT) analyses of all enrolled study populations has not been uniformly reported ( 3 ).…”
mentioning
confidence: 99%